SPECIFIC IMPACT OF CORPORATE CULTURE ON ORGANIZATION STRUCTURE - Anatoly V. Kolesnikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
During the process of company designing its management face the problem of choice between mechanistic and organic types of organizational structures. At this moment it is important to formulate parameters of corporate culture, which would correspond to the chosen type of organizational structure. It could give an opportunity to gain synergy effect, when tools of corporate culture would complement to but not clash with features of the organizational structure. The author widened the tool aspect of interaction between corporate culture and J. Coal organizational structure by new elements and provided graphic interpretation of recommended types of corporate culture in conformity with types of organizational structures of management.